A Community Empowerment Through Motorcycle Reparation Training at Youth Organization - Rahayu Mardikaningsih; Ella Anastasya Sinambela; Didit Darmawan; Samsul Arifin; Jahroni Jahroni; Arif Rachman Putra; M. Syaiful Anwar (Universitas Ahmad Dahlan, 2022)
Background: In Karangtanjung Village, Sidoarjo, the youth and women have solid cadet members. However, so far the activities carried out are of a social nature and do not focus on economic development. Youth organizations in the Karangtanjung Village often receive visits from several universities to provide counseling. However, the visit did not involve training. For this reason, the University of Sunan Giri Surabaya community service team carried out community service activities. This activity aims to provide training on motorcycle engines. Contribution: Economic development from the participation of youth in the village through businesses in the motorbike service sector Method: Direct training to youths and get to know various minor problems on motorbikes. Results: The results of this community service activity can be said to be successful and did not encounter significant obstacles. There were 30 participants who already had an understanding of how to lightly maintain motorbikes and how to carry out motorcycle maintenance and repairs. All residents of Karangtanjung and University of Sunan Giri appreciate the community service activities that have been carried out. Conclusion: Youth organizations have the ability to carry out minor motorcycle repairs which can be used as initial provisions if they are going to become entrepreneurs in the automotive sector